Mobile devices and smart gadgets in medical sciences - Umair, Sajid, 1992- (Advances in medical technologies and clinical practice book series., 2020)
"This book explores advancements and practices in the use of mobile devices, smart gadgets, and other technologies in the medical sciences"--Provided by publisher.